ANALISIS KEAMANAN APPLICATION LOG WEBSITE BERBASIS DASHBOARD MENGGUNAKAN SECURITY INFORMATION AND EVENT MANAGEMENT - Nurulfadhlia; Kasmawi; Pretti Ristra (LPPM Universitas Abdurrab, 2026)
The rapid development of websites as platforms for service delivery and information management has made web application security increasingly important, particularly in monitoring user activities and detecting potential security threats. One important data source in website security is the application log, which records authentication activities and system access. However, most previous studies have focused on analyzing infrastructure logs such as server and network logs, while research that specifically analyzes website application logs and presents them through a centralized security dashboard remains limited. Therefore, this study aims to analyze the security of website application logs using a dashboard-based approach with Security Information and Event Management (SIEM). The system development method employed is the Waterfall model, which consists of requirement analysis, design, implementation, testing, and maintenance stages. The SIEM approach is applied to collect, normalize, correlate, and analyze application log data. The results show that the developed system is able to record and visualize user activities through a security dashboard and detect several types of suspicious activities, including repeated failed login attempts (brute force), access outside operational hours, HTTP error bursts, and access to sensitive routes based on simulation testing. The analysis results are presented in the form of real-time visualizations and risk alerts, facilitating administrators in monitoring and auditing website security. Thus, the proposed dashboard-based application log security analysis system using SIEM can enhance the effectiveness of website security monitoring and support early detection of potential security threats at the web application level.